The effect of resistance training without balance exercises on static balance skill - Mehmet Soyal; Ömür Gülfirat; Aydın Pekel (Physical Education of Students, 2020)
Background and Study Aim: The aim is to evaluate the effect of resistance training without balance exercises on the static balance skill.